Akt determines cell fate through the negative regulation of the PERK-eIF2α phosphorylation pathway - Mounir, Zineb (2011)
Metazoans respond to various forms of environmental stress by inducing the phosphorylation of the α subunit of the translation initiation factor eIF2 at serine 51 (eIF2αP), a modification that leads to a global inhibition of mRNA translation. Herein, we demonstrate that eIF2αP is induced by pharmacological inhibition of the phosphoinositide-3-kinase (PI3K)-Akt pathway as well as by genetic or small interfering (si)RNA-mediated ablation of Akt. Increased eIF2αP is an evolutionary conserved process that involves the endoplasmic reticulum (ER)-resident protein kinase PERK, which is negatively regulated by Akt-dependent phosphorylation at threonine 799. PERK activity and eIF2αP are downregulated by activated Akt in mouse mammary gland tumors as well as in cells exposed to ER stress or oxidative stress leading to the induction of cell survival or death respectively. In unstressed cells, the PERK-eIF2αP pathway guards survival and facilitates adaptation to the deleterious effects of PI3K or Akt inactivation. As such, inactivation of the PERK-eIF2αP arm increases the susceptibility of tumor cells to death by pharmacological inhibitors of PI3K or Akt. Thus, in addition to mTOR the PERK-eIF2αP pathway provides a link between Akt signaling and translational control with implications in tumor formation and treatment.